Corporate Governance and Auditor Quality Choice: Evidence from Palestinian Corporations - Dwekat, Aladdin; Mardawi, Zeena; Abdeljawad, Islam (International Journal of Economics and Financial Issues, 2018)
The aim of this study is to examine the impact of corporate governance mechanisms on auditor quality choice in Palestine. The relationship between corporate governance and auditor quality choice depends on whether Palestinian firms see the quality of auditor as a substitute or a complement to governance practices. The sample included 46 firms listed on the Palestine Stock Exchange (PSE) for the period from 2013 to 2015. Relevant data were collected from the annual reports of the sampled companies published at the PSE website. Auditor's quality was assessed using audit firm size (Big 4 or non-Big 4). To achieve the objectives of this study, a binary logistic regression was used. The results revealed that companies with a high ownership concentration, larger board size and the existence of audit committee tend to hire a high quality auditor. In addition, results showed a significant positive tendency of higher total asset firms to hire a quality auditor while firms with higher leverage tend to choose less quality auditors. Furthermore, director ownership, board independence, CEO duality were found to have no effect on auditor's quality choice. The study recommends that regulators need to encourage companies for more compliance with corporate governance instructions. Keywords: Corporate Governance, Auditor Choice, Palestine JEL Classification: M420